Implementation of routine first trimester combined screening for pre‐eclampsia: a clinical effectiveness study. (1st July 2020) - Guy, GP; Leslie, K; Diaz Gomez, D; Forenc, K; Buck, E; Khalil, A; Thilaganathan, B
Abstract : Objective: Evaluate clinical effectiveness of the first trimester combined (FMF) pre‐eclampsia screening programme when implemented in a public healthcare setting. Design: Retrospective cohort study. Setting: London tertiary hospital from January 2017 to March 2019. Methods: 7720 women screened for pre‐eclampsia according to National Institute for Health and Care Excellence (NICE) risk‐based guidance and 4841 by the Fetal Medical Foundation (FMF) algorithm which combined maternal risk factors, blood pressure, PAPP‐A and uterine artery Doppler indices in the first trimester. High risk was defined by standard NICE criteria in the pre‐intervention cohort (prescribed 75 mg aspirin) or a risk of ≥1:50 for preterm pre‐eclampsia from the FMF algorithm in the post‐intervention cohort (prescribed 150 mg aspirin). Main outcome measures: Screening effectiveness, rates of pre‐eclampsia. Results: The FMF screening programme resulted in a significant reduction in the screen‐positive rate (16.1 versus 8.2%, odds ratio [OR] 0.50, 95% confidence interval [CI] 0.41–0.53) with a concurrent increase in targeted aspirin use in women classified as high risk for pre‐eclampsia (28.9 versus 99.0%, OR 241.6, 95% CI 89.6–652.0). Screening indices were uniformly improved for the FMF algorithm with receiver operating characteristic (ROC) analysis demonstrating excellent discrimination for preterm pre‐eclampsia (area under the curve [AUC] = 0.846, 95% CI 0.778–0.915, P value <.001). Interrupted time series analysis showed that the FMF screening programme resulted in a significant 21‐month relative effect reduction of 80% ( P = .025) and 89% ( P = .017), for preterm and early pre‐eclampsia, respectively. Conclusions: First trimester combined screening for pre‐eclampsia is both feasible and effective in a public healthcare setting. Such an approach results in a two‐fold de‐escalation of risk, doubling of pre‐eclampsia detection, near total physician compliance of aspirin use and a significant reduction in the prevalence of preterm pre‐eclampsia. Tweetable abstract: Implementation of 1st trimester combined pre‐eclampsia screening effectively reduces prevalence of the disorder. Tweetable abstract: Implementation of 1st trimester combined pre‐eclampsia screening effectively reduces prevalence of the disorder. This article includes Author Insights, a video abstract is available at https://vimeo.com/rcog/authorinsights16361